Pengaruh Brand awareness dan Celebrity endorsement terhadap Minat Beli Produk Skincare Glad2Glow (G2G): Studi Kasus Pada Gen Z di Kota Bandung - Viena Pebrianti; Aldy Santo Hegiarto (MAN 4 Kota Pekanbaru, 2026)
Indonesia’s skincare industry is growing rapidly, leading to increasingly intense market competition. Many skincare brands now rely on brand awareness and celebrity endorsement to attract consumer purchase intention, especially among Generation Z. This study aims to determine the extent to which brand awareness and celebrity endorsement influence purchase intention toward Glad2Glow (G2G) skincare products among Generation Z in Bandung City. A quantitative method with an explanatory approach was used, involving 100 respondents selected through purposive sampling, with data analyzed using multiple linear regression assisted by IBM SPSS Statistics version 25. The results show that brand awareness has a very strong correlation with purchase intention (r = 0.903), and celebrity endorsement also demonstrates a very strong correlation (r = 0.901). Together, both variables account for 86% of the variation in purchase intention (R² = 0.860), with a positive and significant effect both partially and simultaneously. This study is expected to help companies design more targeted digital marketing strategies.